Postoperative Antibiotics and Their Effect on Postoperative Infection after ORIF - Nichols, Emma Hitt (MD Conference Express, 2014)
Surgical treatment of fractures is common, and therefore it is important to understand which approaches are most effective in reducing postoperative infections for these procedures. This article presents the results of a study of postoperative antibiotics for open reduction and internal fixation surgery for closed fractures [NCT00610987].